Effects Of Herbicide Use Alone And In Combination On Weeds And Transplanted Rice Under Temperate Conditions Of Kashmir (Applied Biological Research, 2011)
Field experiments were conducted during kharif seasons of 2006 and  2007 at Rice Research and Regional Station, SKUAST-K, Khudwani,  Anantnag (India) on a silty clay loam soil, normal in reaction. The study  revealed that herbicides flufenacet @ 90 g ha-1, application of butachlor  1.5 kg followed by chlorimuron ethyl + metsulfuron methyl 4 g ha-1and  butachlor 1.5 kg followed by bensulfuron methyl 50 g ha-1recorded  significantly higher number of panicles, grains panicle-1and grain and straw yields through better weed control as indicated by lower weed  density and reduced weed dry matter as compared to other herbicidal  treatments. On an average, flufenacet application gave 8.1 and 46.7%  more grain yield over butachlor and weedy check treatments,  respectively. Chlorimuron ethyl + metsulfuron methyl provided good  control of broad leaved weeds and sedges, while bensulfuron-methyl was  effective against sedges.
Keywords: Butachlor; bensulfuron-methyl; chlorimuron ethyl; flufenacet; herbicides; metsulfuron methyl; rice; weeds